PERFORMANCE ANALYSIS OF OPTICAL WIRELESS COMMUNICATION SYSTEM DESIGNED BY USING DIFFERENT FILTERS - İmak, Fethiye Merve Kavak; Kaya, Duygu (My University, 2024)
Free space optical communication (FSO) technology, which has been developing in recent years, is advantageous compared to other wireless communication technologies due to its features such as high bandwidth, low latency, and high security. Since the FSO system is sensitive to atmospheric events, it needs various signal processing and filtering techniques to reduce the deterioration in the quality of the signal. The FSO free space channel has several channel types, such as the scattered channel and the optical wireless communication (OWC) channel. In this study, comparisons were made using various filters in an FSO system designed using the optical wireless communication (OWC) transmission channel model, and the system was analyzed based on the results obtained.
Keywords: Optical wireless communication (OWC); free space optical communication (FSO); bit error rate (BER); q factor; optical filter